Battles for branding: a political marketing approach to studying televised candidate debates. Issue 3 (27th May 2021) - Bramlett, Josh C.
ABSTRACT: Political debates provide candidates the opportunity to brand themselves to voters. Through an analysis of survey responses from participants who viewed one of two 2018 U.S. Senate debates, the current study incorporates a political marketing perspective to analyze how televised political debates influence voters' brand associations toward candidates. This study introduces the concept of Debate Candidate Branding, where participating in a debate is more likely to generate positive associations with supporters than it is to generate negative associations with detractors. Each of the candidates in this study saw more positive in-group associations than negative out-group associations, highlighting the potential of debates as branding opportunities. Moreover, brand favorability, i.e., how many positive or negative thoughts individuals had toward candidates, was significantly associated with changes in candidate evaluations. Additionally, respondents offered more brand associations about the candidates as people than they did about the policy positions or party affiliation of the candidates.